Arsenic leaching and speciation in C&D debris landfills and the relationship with gypsum drywall content. (January 2017) - Zhang, Jianye; Kim, Hwidong; Dubey, Brajesh; Townsend, Timothy
Graphical abstract: Highlights: Arsenic leaching and speciation in C&D debris landfills was investigated. Arsenic leaching decreased with increasing sulfide up to about 1000 μg/L. Arsenic leaching increased when sulfide is greater than 1000 μg/L. The formation of thioarsenic ions at high S 2− (>1000 μg/L) favors arsenic leaching. Abstract: The effects of sulfide levels on arsenic leaching and speciation were investigated using leachate generated from laboratory-scale construction and demolition (C&D) debris landfills, which were simulated lysimeters containing various percentages of gypsum drywall. The drywall percentages in lysimeters were 0, 1, 6, and 12.4 wt% (weight percent) respectively. With the exception of a control lysimeter that contained 12.4 wt% of drywall, each lysimeter contained chromated copper arsenate (CCA) treated wood, which accounts for 10 wt% of the C&D waste. During the period of study, lysimeters were mostly under anaerobic conditions. Leachate analysis results showed that sulfide levels increased as the percentage of drywall increased in landfills, but arsenic concentrations in leachate were not linearly correlated with sulfide levels. Instead, the arsenic concentrations decreased as sulfide increased up to approximately 1000 μg/L, but had an increase with further increase in sulfide levels, forming a V-shape on the arsenic vs. sulfide plot. The analysis of arsenic speciation in leachate showed different species distribution as sulfide levels changed; the fraction of arsenite (As(III)) increased as the sulfide level increased, and thioarsenate anions (As(V)) were detected when the sulfide level further increased (>10 4  μg/L). The formation of insoluble arsenic sulfide minerals at a lower range of sulfide and soluble thioarsenic anionic species at a higher range of sulfide likely contributed to the decreasing and increasing trend of arsenic leaching.